PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS II SD NEGERI 171 PEKANBARU - Herwinda, Hebra; Marhadi, Hendri; Alim, Jesi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of the problems in this study is the low student learning outcomes IPS seen from the completeness of student learning outcomes with KKM 74 from 35 students who reach KKM only 16 students that is only about 45.7% and that does not reach the KKM is 19 students yatu approximately 54.3% with the average value of 67.8%. This is because the teachers only use the lecture method, question and answer and assignments so that students are less active in the learning process, only students with high academic abilities are active to answer the question, while the less intelligent students only passive so that the material obtained by the students do not last long in memory. The study aims to improve learning outcomes IPS grade II Elementary School 171 Pekanbaru with the implementation of cooperative learning model make a match. The study design used is classroom action research (PTK) is conducted in two cycles. Each cycle consists of two meetings and one-time delivery of content meeting the daily tests. So that action research is successful, the researchers set the stage that action planning, action, observation and reflection. Based on the research results, it could be concluded that an increase in learning outcomes seen in the average value of the basic score is 67.8% increased by 18.4 points to 86.2% in UH I then increased again by 4.2 points to 90.4% at UH II, exceeds the criteria set at 85%. Application of Cooperative Learning Model Make A Match To Improve Learning Outcomes IPS Grade II SD Negeri 171 Pekanbaru.Key Words : Application of Cooperative Learning Model Make A Match, IPS Learning Outcomes.2